Mobile Authentication Problems and Solutions - Jakobsson, Markus; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2013)
Mobile Authentication: Problems and Solutions looks at human-to-machine authentication, with a keen focus on the mobile scenario. Human-to-machine authentication is a startlingly complex issue. In the old days of computer security-before 2000, the human component was all but disregarded. It was either assumed that people should and would be able to follow instructions, or that end users were hopeless and would always make mistakes. The truth, of course, is somewhere in between, which is exactly what makes this topic so enticing. We cannot make progress with human-to-machine authentication without understanding both humans and machines. Mobile security is not simply security ported to a handset. Handsets have different constraints than traditional computers, and are used in a different way. Text entry is more frustrating, and therefore, it is tempting to use shorter and less complex passwords. It is also harder to detect spoofing. We need to design with this in mind. We also need to determine how exactly to integrate biometric readers to reap the maximum benefits from them. This book addresses all of these issues, and more.
The Big Picture -- The Benefits of Understanding Passwords -- Your Password is Your New PIN -- Like Passwords - But Faster, Easier and More Secure -- Improved Visual Preference Authentication -- How to Kill Spoofing -- Can Biometrics Replace Passwords? -- Legacy Servers: Teaching Old Dogs New Tricks.
Keywords: Computer science; Computer Communication Networks; Data protection; Data structures (Computer science).; Data encryption (Computer science).; Biometrics; Computer Science; Systems and Data Security; Biometrics; Computer Communication Networks; Data Encryption; Data Structures, Cryptology and Information Theory